EMIGRATION LITERARY STUDY OF YURI STEFANYK: FINISHES TO THE PORTRAIT OF THE RESEARCHER (BASED ON A FOREIGN PERIODICAL) - Hrytsyuk, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article analyzes the emigration literary, publishing and public activities of Yuriy Stefanyk basedon Ukrainian-language foreign periodicals published in the end of the XX c. In Canada (it included such periodicals as «Ukrainian News», «Svoboda», «Homin of Ukraine», «New Way»). The question of returning and deepening the figure of Yuriy Stefanyk in modern literary science remains relevant today. In this study, we set ourselves the goal of drawing a portrait of Yuriy Stefanyk based on articles by U. Samchuk, Y. Boykо, P. Savarуn, D. Nytchenko, I. Kachurovsky, and other sin Canadian periodicals («Svoboda», «Ukrainian News», «Ukrainian Voice», «Ukrainian Edmonton», «Homin», etc.) and trace the reception of his scientific and other activities through the prism of published articles, notes, essays, memoirs. The research method involves the use of biographical, psychological methods, methods of text analysis and hermeneutics in the process of work. The novelty of the article lies in the fact that the figure of Yuriy Stefanyk is highlighted systematically and in general, from the pointofview of foreign journalism, almost for the first time. Practical significance and obtained results. As a result, a literary portrait of Yuriy Stefanyk against the background of the era is demonstrated. The material of the article can be used as a supplement to literary courses dealing with the issues of Stefanyk studies, emigration literary studies, and literary criticism.